Social work with people with learning difficulties. - Williams, Paul (Lecturer); Evans, Michelle (Thousand Oaks, Calif. : Sage/Learning Matters, 2013)
Part of the Transforming Social Work Practice series, this title intends to support students on the social work degree. It seeks to confirm and strenghten social work values and principles so that the progress and successes achieved by'Valuing People' can continue.
Machine generated contents note: ch. 1 Who are {u1C25}ople with learning difficulties'? -- ch. 2 The importance of values: a historical account -- ch. 3 Policy and legislation -- ch. 4 The role of the social worker -- ch. 5 Working with children and families -- ch. 6 Working with adults -- ch. 7 Assessment, planning and evaluation -- ch. 8 Communication and sensory needs -- ch. 9 Advocacy and empowerment.
Previous ed.: 2009.
Includes bibliographical references and index.
Keywords: Social work with people with mental disabilities -- united Kingdom; Social work with people with mental disabilities -- united Kingdom -- Case studies; Learning disabled -- Services for -- united Kingdom